2010
DOI: 10.1523/jneurosci.4346-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/Calmodulin-Dependent Protein Kinase IIα Is Required for the Initiation and Maintenance of Opioid-Induced Hyperalgesia

Abstract: Repeated administration of opioids not only leads to tolerance and dependence, but also results in nociceptive enhancement called opioid-induced hyperalgesia (OIH). Nociceptive mediators involved in OIH generation remain poorly understood. In the present study, we tested the hypothesis that Ca 2ϩ /calmodulin-depent protein kinase II (CaMKII␣) is critical for OIH. Opioid-induced hyperalgesia was produced by repeated morphine administration or pellet implantation in mice. Correlating with the development of tact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 69 publications
6
91
0
1
Order By: Relevance
“…Prefrontal cortex sections were quickly dissected on ice and frozen on dry ice for western blotting analysis as described previously (Luo et al, 2008;Chen et al, 2010). Tissues were homogenized in ice-cold radioimmunoprecipitation assay buffer in the presence of protease inhibitors and phosphatase inhibitors and centrifuged.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prefrontal cortex sections were quickly dissected on ice and frozen on dry ice for western blotting analysis as described previously (Luo et al, 2008;Chen et al, 2010). Tissues were homogenized in ice-cold radioimmunoprecipitation assay buffer in the presence of protease inhibitors and phosphatase inhibitors and centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work by our laboratory and others demonstrated that Ca 21 /calmodulin-dependent protein kinase II a (CaMKIIa) is critically important for the development and maintenance of opioid tolerance, opioid dependence, and opioid-induced hyperalgesia (Chen et al, 2010). CaMKIIa is a multifunctional serine/ threonine protein kinase that is abundantly expressed in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…We complemented this data by analyzing the expression of two kinase isoforms, PKA-RIIβ and CaMKIIα, involved in pain sensitization of nociceptors (Brüggemann et al, 2000;Chen et al, 2010;Isensee et al, 2014a). With the exception of CaMKIIα, all marker proteins were already detectable at birth, but changed their cellular expression pattern during aging ( Figs 2B and 3).…”
Section: Basal Characterization Of Sensory Neurons Rats From P0 To 24mentioning
confidence: 96%
“…phosphorylates, and thereby modulates, ion channels including TRPV1, and has been implicated in pain regulation (Chen et al, 2010;Ferrari et al, 2013Ferrari et al, , 2014Hucho et al, 2012;Jung et al, 2004). Microarray data suggest that CaMKIIα mRNA is upregulated fivefold between neonatal and adult DRG neurons (Zhu and Oxford, 2011), but measurements at the protein level are missing.…”
Section: Camkiiα Expression Develops Postnatally and Is Maintained Thmentioning
confidence: 99%
“…. Other targets" calcium-modulating serine/threonine protein kinase present in the CNS, Ca 2+ /calmodulin protein kinase II CaMKII , has been of recent interest as a modulator of neuropathic pain and is an important contributor to initiation and maintenance of opioid-induced hyperalgesia [94]. Recently, in a limited clinical trial, 18 SCD patients were treated with single dosage of triluoperazine a CaMKII inhibitor going up to 10 mg, and eight subjects reported almost 0% reduction in their chronic pain.…”
mentioning
confidence: 99%